Influence of Salvia miltiorrhizae on the Mesenteric Lymph Node of Rats with Severe Acute Pancreatitis or Obstructive Jaundice - Zhang Xiping; Zhang Jie; Ye Shuyun; Wang Qili; Feng Guanghua; Pan Yan (Mediators of Inflammation)
Objective. To observe the effect of salvia miltiorrhizae injection on inflammatory mediator levels and mesenteric lymph nodes in severe acute pancreatitis (SAP) and obstructive jaundice (OJ) rats and explore the protective mechanism of salvia miltiorrhizae on the lymph nodes of these rats. Methods. A total of 288 rats were used in SAP-associated and OJ-associated experiments. The rats were randomly divided into sham-operated group, model control group, and treated group. At various time points after operation, the pathological changes in mesenteric lymph nodes of rats in each group were observed, respectively. Results. The pathological severity scores in lymph nodes of SAP rats in treated group were significantly lower than those in model control group (P<.05) while the pathological changes in lymph nodes of OJ rats in treated group also showed varying degrees of mitigation. Conclusion. Salvia miltiorrhizae can exert protective effects on the lymph nodes of SAP or OJ rats via a mechanism that is associated with reducing the contents of inflammatory mediators in blood.